Algorithm of selection of acetabular component of hip joint endoprothesis in patients with femoral head aseptic necrosis. - A. Ye. Loskutov; A. Ye. Olejnik; A. V. Altanets; Ye. A. Kovbasa (Medičnì Perspektivi)
The article represents a comparative roentgenmorphometric analysis of hip joint deformation development in femoral head aseptic necrosis (FHAN) that was done to identify criteria which determine the selection of the acetabular component of the total hip joint endoprosthesis. There were analysed 234 hip joint radiograms of patients with FHAN performed in anterior-posterior plane. Radiograms were subdivided into 3 groups concerning staging of the process: stage II – 18 radiograms, stage III – 84 radiograms, stage IV – 132 radiograms. Analyzing the acetabular retraction (AR) following indices were assessed: sphericity coefficient  α (α = r/d), proportionality coefficient β (β = n/r), compliance coefficient γ (γ = h/r), where r – radius of the acetabulum, n – thickness of the acetabular bottom, h – height of the “Napoleon’s hat”. In addition, there was assessed presense of the major trabecular structures of the supra-acetabular area (A,B,C). Score assessment system, based on the identified indices of changing tendencies in FHAN was offered. There were determined the first level criteria, characterizing the acetabular and supra-acetabular area state. Besides, individual factors of the patient (sex, age) which substantially determine endoprosthesis stability in the remote postoperative period were related to second level criteria. Basing on the assessment of the first and second level criteria algorithm of choice of the total hip endoprosthesis component was developed. Thus, developed system of choice of total hip endoprosthesis component which consider peculiarities of the acetabular deformation formed in the late stages of FHAN assesses the ability of the supra-acetabular area to perceive loading. In addition algorithm takes into consideration individual factors of the patient (sex, age) by the moment of implantation, which determine total hip endoprosthesis stability in the latest postoperative period and consequently the risk for aseptic instability development.